2005
DOI: 10.1021/jp050534s
|View full text |Cite
|
Sign up to set email alerts
|

Competing Non-covalent Interactions in Alkali Metal Ion−Acetonitrile−Water Clusters

Abstract: Competitive ion-dipole, ion-water, and water-water interactions were investigated at the molecular level in M+ (CH3CN)n(H2O)m cluster ions for M = Na and K. Different [n,m] combinations for two different n + m cluster sizes were characterized with infrared predissociation spectroscopy in the O-H stretch region and MP2 calculations. In all cases, no differences were observed between the two alkali metal ions. The results showed that at the n + m = 4 cluster size, the solvent molecules interact only with the ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
3
25
1
Order By: Relevance
“…There are some features in the baseline which we do not fully understand the cause of, that precede gross reduction. The step at -0.7 V (vs. Ag/AgCl) is probably not negative enough to be free water reduction, but it could more plausibly be the reduction of trace water coordinated to the metal cation-although [36] has stated that acetonitrile will strongly compete with water in the solvation sphere around metal cations in acetonitrile-water mixtures. The small peak at about À2.2 V (vs. Ag/AgCl) in the potassium and cesium solutions may be due to specific adsorption of these relatively polarisable ions, a limited intercalation event or possibly contamination.…”
Section: Electrochemical Windowmentioning
confidence: 99%
“…There are some features in the baseline which we do not fully understand the cause of, that precede gross reduction. The step at -0.7 V (vs. Ag/AgCl) is probably not negative enough to be free water reduction, but it could more plausibly be the reduction of trace water coordinated to the metal cation-although [36] has stated that acetonitrile will strongly compete with water in the solvation sphere around metal cations in acetonitrile-water mixtures. The small peak at about À2.2 V (vs. Ag/AgCl) in the potassium and cesium solutions may be due to specific adsorption of these relatively polarisable ions, a limited intercalation event or possibly contamination.…”
Section: Electrochemical Windowmentioning
confidence: 99%
“…For this particular mixed solvent system, it is quite possible that the profile of the intensity distribution is strongly influenced by the relative binding energies of the molecules concerned, and we shall return to a discussion of this point later. Work on singly charged mixed solvent systems by Vaden and Lisy has shown that although coordination numbers in the gas phase for systems capable of hydrogen bonding are often lower than in the condensed phase they are very dependent on ion-ligand interactions and thus, by varying the ratio of solvents, direct coordination to the central metal ion can be modified [11,12].…”
Section: Precursor Ion Intensity Distribution Ofmentioning
confidence: 99%
“…From simulations of an ion in the presence of water and methanol they concluded that a positively charged solute exhibits a pronounced preference for water. If there are large differences in the solvating abilities of the components, selective or preferential solvation may occur [11,12]; however, the degree of averaging present in a typical condensed phase system means that subtle effects due to small differences in free energy are unlikely to make their presence felt [13]. In contrast, the consequences of small, individual differences in molecular properties can be amplified in the gas phase because of the influence they may have on establishing equilibria or determining fragmentation pathways [10, 19 -21].…”
mentioning
confidence: 99%
“…186 Benzene was used as a surrogate for tyrosine, an amino acid which lines the selectivity region of most potassium ion channels. 188 No significant hydrogen-bonding interactions were observed until four waters were present. This behavior was not observed for Na + -bearing cluster ions, thus, demonstrating that ion size selectivity was possible via the cation-interaction.…”
Section: Synergymentioning
confidence: 99%